Investigating the effect of adding combination of polyester and crushed glass on the hot mix asphalt mixture - لينا قادي; عبد الرحمن سلمان; ضياء عودة; نوال بدران; يوسف ضميدي (My University, 2024)
Due to the continuous increase in road traffic volumes and expensive maintenance costs of streets and relevant traffic components, combined with lack of funds and professional supervision, the invention, creation, and discovery of new and novel technologies and components are becoming an urgent necessity. On the other hand, developing countries such as Palestine faces many problems in roads such as rutting and cracking, and the use of polyester and crushed glass which is environmentally friendly and has low impact compared with other traditional engineering solutions may offer a promising prospect. There are two different methods for mixing polyester and crushed glass with bitumen, either dry mixing or wet mixing. In this study, the project team studied the use of dry method (Marshal method) for asphalt mixture along with ¾ inch hot mix asphalt and medium traffic, where the materials required for the mixture were prepared, then samples were formed with different proportions of crushed glass and polyester, then tests were conducted considering both materials and the results were compared with the normal HMA mixture. The results indicated that polyester and crushed glass additives improved the properties of asphalt mixture. As expected, after adding a certain percentage of crushed glass and polyester, the properties of the asphalt mixture were improved, in term of the stability, strength and durability. It is expected also it decrease rutting, cracking, and shoving and improve fatigue resistance, permanent deformation and stiffness. According to the results, the specifications are achieved at 15% from combination of polyester and crushed glass